Online-Based Violence Against Children: Efforts to Develop Child Protection Strategies in the Digital Era in Magelang Regency - Triantono; Muhammad Marizal; Natasya Okta Setiani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
The rapid advancement of technology has resulted in the exponential transformation of social interactions and relations. The ease of access and broad reach have increased internet penetration, particularly among children aged 13-17 in Magelang Regency. While this situation can have positive impacts, the low level of literacy and awareness of the use of digital devices has increased the risk of online-based violence against children. This research focuses on three issues: the conditions and dynamics of online-based violence against children in Magelang Regency, the measures already taken to respond to online-based violence against children in Magelang Regency, and prevention strategies for online-based violence against children from the perspective of fulfilling children's rights and protection in the future. This study employs a qualitative approach with children aged 13-17 years. The research findings reveal that children aged 13-17 years in Magelang Regency experience two forms of violence: cyberbullying and sexual harassment. Low digital media literacy and risky interaction behaviours, coupled with inadequate mitigation efforts, pose a significant potential for an increase in this type of violence in the future. There are seven prevention strategies: digital literacy for children and parents; safe environment and technology; accessibility of services; strengthening regulations and child protection institutions; strengthening coordination and synergy; public awareness; and parental/family participation.